KOMPONEN-KOMPONEN PEMBELAJARAN AL-KITÂBAH BAHASA ARAB - Huda, Nurul (Al Mah?ra: Jurnal Pendidikan Bahasa Arab, 2016)
The main component of Arabic learning covers the same four language skills for all competencies. They are: listening (istimâ’), speaking (kalâm), reading (qirâ’ah), and writing (kitâbah). Those four skills mutually connected. For instance, listening skill contributes to speaking skill and vice versa. In turn, those two skills will be strengthened by student reading skill or vice versa. Speaking skill is very close related to listening skill.  Speaking and listening skill refer to all means to communicate orally. Because of the importance of this writing skill, the writer sees the need of al-Kitabah study map and its parts that can be delivered to student systematically, start from the lowest level (Ibtidâiyyah) to the next level (I’dadiyyah) based on students condition and psychology, including components in Al-kitâbah.